State of art of mobility medicine: some more abstracts and evidence that the success of Pdm3 is based on extra-session relationships - Ugo Carraro; Marie Sophie Alberty; Stephen Anton; Elena Barbieri; Ines Bersch; Gerardo Bosco; Daniele Coraci; Paolo Gargiulo; Paulo Gentil; Ashraf S. Gorgey; Maria Chiara Maccarone; Winfried Mayr; et al. (PAGEPress Publications, 2024)
Scientific conferences increasingly suffer from the need for short presentations in which speakers like to dwell on the details of their work. A mitigating factor is to encourage discussion and planning of collaborations by organizing small meetings in a hotel large enough to host all attendees. This extends discussions' opportunities during morning breakfasts, lunches, dinners and long evenings together. Even if the vast majority of participants will not stay for the entire duration of the Conference, the possibilities for specialists to interact with specialists who are even very distant in terms of knowledge increase enormously. In any case, the results in terms of new job opportunities for young participants outweigh the costs for the organizers. Thirty years of Padova Muscle Days offer many examples, but the authors of this report on the state of the art of Mobility Medicine testify that this also happened in the 2024 Five Days of Muscle and Mobility Medicine (2024Pdm3) hosted at the Hotel Petrarca, Thermae of Euganea Hills and Padua, Italy which is in fact a valid countermeasure to the inevitable tendencies towards hyperspecialization that the explosive increase in scientific progress brings with it.